SHORTCUT TO BECOME A DIGITALPRENEUR - Lambok Rommy Suleman; Rizaldi Putra; Ade Oki Pebiansyah; Deni Utama; Nurali, Nurali; Muhamad Yusup; Irham Purnamasidi (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
The rapid digital development in Indonesia and the high use of the internet in the business world do not make it easy for a prospective digitalpreneur to start a business. The limitation of ideas and capital is a scourge that often butchers when you want to start a business. The targeted output results from the implementation of this activity are an increase in the knowledge of employees, interns and ex-interns, especially in terms of choosing the right use of capital in starting a business, developing a business and managing a business, making a tagline that matches the business created, creating viral content so that the public is aware of the products or services marketed by participants. The results of the activity show that the increase in knowledge and understanding of employees, interns and ex-interns has increased, which can be seen from the material for making Taglines increased from 60% to 86.70%, then after the delivery of the material for making viral content the participants' understanding also increased from previously only 60% to 93.33%.